Gambaran Umum Lagoftalmus - Fityah Zabrina Hidayat; Putu Ristyaning Ayu Sangging; Rani Himayani (Medula, 2023)
Lagophthalmos is a disorder of the eyelids that cannot close completely. Lagophthalmos causes the eyes to remain open and unable to blink, this causes the eyes to have no protection so they can be exposed and leading them to evaporating the tears. The impact that arises is damage to the layers of the eye and will continue to get worse if it is not treated immediately. Lagophthalmos has many etiologies. Nevertheless, the main cause of lagophthalmos is facial nerve paralysis (N.VII) which is also known as paralytic lagophthalmos, damage to the eyelids which is called cicatricial lagophthalmos, and lagophthalmos during sleep which is called nocturnal lagophthalmos. Diagnosis can be established by anamnesis and physical examination results. The patient will complain of a foreign object in the eye, as well as a feeling of soreness, the eye can be watery or dry, and if lagophthalmos is accompanied by damage to the cornea, blurry vision can be found. On physical examination, a gap will be found between the upper and lower eyelids when the patient tries to close his eyes. Physical examination and laboratory tests can also be used to determine the etiology of lagophthalmos and rule out the differential diagnosis. Other physical examinations that can be carried out are function tests of all cranial nerves and corneal sensitivity tests. Treatment for lagophthalmos is divided into pharmacology and surgery according to the severity of the disease. There are also preventive efforts made to relieve symptoms and prevent the severity of the disease with education.